The potential harms of goodwill impairment avoidance: Evidence based on future performance and stock prices - Hongwen Han; Qingquan Tang (China Journal of Accounting Research, 2020)
The rapidly increasing volume of goodwill assets in the capital market generates potential risks due to the possibility of an untimely recognition of goodwill impairment. In this paper, we investigate the financial consequences of goodwill impairment avoidance based on firms' future performance and stock prices. Using Chinese A-share listed firms with goodwill balances, we find that avoiding goodwill impairments negatively affects a firm's performance growth and increases its risk of a future stock price crash. These adverse effects continue for the three years following the goodwill impairment avoidance. Our results indicate that goodwill impairment avoidance has detrimental impacts on a firm's future performance and stock price and that these impacts are persistent. Our conclusions are helpful for regulators on how to prevent the risks hidden in goodwill impairment recognition and maintain the stable development of the financial market.
Keywords: 650; Firm performance; Goodwill impairment avoidance; Persistence; Stock price crash risk